Don't lie to me : and stop trying to steal our freedom - Pirro, Jeanine (Center Street, 2020)
"It's been nearly four years since President Trump took office, and Judge Jeanine Pirro has had enough of the left's countless lies and false accusations. She is now forced to ask: How could anyone vote against President Trump this November? What more could you possibly want? In Don't Lie to Me, Judge Jeanine brings her signature writing style and acute legal mind to topics such as the impeachment inquiry, the military, and the road to the 2020 presidential election. She will highlight President Trump's triumphs and his strength during the coronavirus crisis."--Amazon.